Fasting Insulin and Risk of Overall and 14 Site-Specific Cancers: Evidence From Genetic Data - Zhang, Han; Li, Doudou; Liu, Xiaozhuan; Wan, Zhongxiao; Yu, Zengli; Wang, Yuming; Li, Xue (Frontiers in Oncology, 2022)
Objective: Whether fasting insulin (FI) plays a causal role in cancer risk remains unclear. This study aimed to investigate the causal association between FI and cancer risk and to explore its potential mediator role in association between type 2 diabetes mellitus (T2DM) and cancer. Methods: Two-sample mendelian randomization (TSMR) analysis was performed to evaluate the causal effect of FI on overall and 14 site-specific cancers using genome-wide association study (GWAS) summary level data from MAGIC and consortia of 14 site-specific cancers. Primary MR approach was conducted by using random-effect inverse variance weighted (IVW) method and sensitivity analyses were implemented by adopting weighted-median, weighted-mode, MR-Egger and MR-PRESSO test. Polygenic risk score analysis was executed by using individual-level data from UK Biobank to validate the findings from TSMR analyses. Multivariable mendelian randomization (MVMR) were carried out to estimate the mediation effect of FI on the association between T2DM and cancer. Results: TSMR study suggested that genetically predicted high FI levels were causally associated with increased risk of colorectal cancer (odds ratio (OR)=1.87, 95% confidence interval (95% CI): 1.23-2.84, P=0.003) and endometrial cancer (OR=1.89, 95%CI: 1.08-3.01, P=0.008), but not associated with overall cancer risk or the other 12 studied cancer sites. Polygenic risk score analysis successfully replicated the association between genetic liability to high FI levels and the increased risk of colorectal and endometrial cancer. MVMR and MR mediation analysis detected an intermediary effect of FI and quantified that FI mediated 21.3% of the association between T2DM and endometrial cancer. Conclusions: This study demonstrated that FI levels are causally associated with the risk of colorectal and endometrial cancer, and FI was found to play an intermediary role in the association between T2DM and endometrial cancer. The causal associations between FI and other cancers need to be further studied.